Women, periodicals, and print culture in Britain, 1890s-1920s : the modernist period - Binckes, Faith; Snyder, Carey J. (Edinburgh history of women's periodical culture in Britain., 2019)
This collection highlights the contributions of women writers, editors and critics to periodical culture in the late nineteenth and early twentieth centuries. It explores women's role in shaping conversations about modernism and modernity across varied aesthetic and ideological registers, and foregrounds how such participation was shaped by a wide range of periodical genres. The essays focus on well-known publications and introduce those as yet obscure and understudied - including middlebrow and popular magazines, movement-based, radical papers, avant-garde titles and classic Little Magazines. Examining neglected figures and shining new light on familiar ones, the collection enriches our understanding of the role women played in the print culture of this transformative period.